Survival of Campylobacter jejuni on fresh spinach stored at 4 °C or 12 °C. (April 2015) - Guévremont, Evelyne; Lamoureux, Lisyanne; Ward, Pierre; Villeneuve, Sébastien
Abstract: There is a growing concern that fresh or minimally processed vegetables can propagate pathogenic bacteria. Vegetables can be contaminated before harvest or throughout handling. The survival of Campylobacter jejuni strains on spinach under different conditions was evaluated in order to see if all strains have the same persistence behavior. Fresh spinach was inoculated with one of eight different strains of C. jejuni . Bacterial survival was measured and compared against temperatures and storage times. At a 12 °C temperature, a significant average decrease of 0.3 log cfu/g in the bacterial populations was observed in comparison with 4 °C. The average population decrease for the tested parameters varied significantly between strains, ranging from 0.1 to 2.4 log cfu/g, regardless of whether the tested strain was of water or bovine origin. Except for two strains, all the strains had a unique genomic fingerprinting profile as evaluated using flaA typing. C. jejuni strains of different animal or environmental origin were able to survive on spinach under the tested storage time and temperature conditions. Storage parameters and bacterial strain can influence the fate of the bacteria on fresh spinach and a significant contamination can represent a threat to human health. Highlights: The ability to survive on fresh spinach was evaluated for eight Campylobacter jejuni strains. Two temperatures and time of storage were evaluated. C. jejuni population decrease was lower at 4 °C than 12 °C. Differences in survival were observed between the tested strains.